Enhanced Efficacy and Broadening of Antibacterial Action of Drugs via the Use of Capped Mesoporous Nanoparticles. Issue 34 (9th July 2013) - Mas, Núria; Galiana, Irene; Mondragón, Laura; Aznar, Elena; Climent, Estela; Cabedo, Nuria; Sancenón, Félix; Murguía, José Ramón; Martínez‐Máñez, Ramón; Marcos, María D.; Amorós, Pedro
<x xml:space="preserve">Abstract</x> Bug busters: A novel nanodevice consisting of mesoporous nanoparticles loaded with vancomycin and capped with ε‐poly‐L‐lysine (ε‐PL) was prepared and its interaction with different Gram‐negative bacteria studied (see figure). A remarkable improvement in the efficacy of the antimicrobial drug ε‐PL and a broadening of the antimicrobial spectrum of vancomycin is demonstrated.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>